Environmental Filtering Effect Drives the Plant Species Distribution in Alpine Grasslands on the Qinghai‐Tibetan Plateau - Yikang Cheng; Ding Li; Nadia I. Maaroufi; Jianling You; Wen Zhou; Wensheng Liu; Danhui Qi; Xiang Liu; Yuguo Wang; Xiaoyun Pan; Wenju Zhang; Ji Yang; et al. (Ecology and Evolution)
ABSTRACT Exploring community assembly is essential for understanding the mechanisms of biodiversity maintenance and species coexistence. In general, stochastic (e.g., dispersal limitation) and deterministic (e.g., environmental filtering) effects have been identified as the two key processes driving community assembly. However, the relative contributions of these two processes and how they vary across different spatial scales remain poorly understood, especially for the high‐diversity grassland ecosystems on Qinghai‐Tibetan Plateau (QTP), which plays a critical role in global climate regulation. In this study, a total of 27 study sites were established along a north–south transect and a west–east transect across the eastern QTP; the two furthest sites were more than 1000 km apart. We analyzed the taxonomic, functional, and phylogenetic diversity and structure of these communities to elucidate the relative importance of dispersal limitation and environmental filtering effects that shape plant distributions at the regional (i.e., encompassing all sites) and the transect scales. A total of 181 species belonging to 99 genera and 34 families of vascular plants were found across all sample sites. Both at the regional and the transect scale, environmental variables were shown to account for a larger proportion of the variation in species composition than spatial variables. Likewise, the plant species diversity (i.e., taxonomic, functional, and phylogenetic diversity) was also primarily influenced by soil and climatic variables rather than by spatial factors. Specifically, mean annual precipitation, mean annual temperature, and soil total carbon content emerged as critical determinants of plant species diversity at the regional scale, while the mean annual temperature was identified as the most important factor at the transect scale. Our results highlight the significance of environmental filtering, rather than dispersal limitation, in shaping plant community dynamics across various spatial scales within the alpine grassland ecosystem, which has crucial implications for plant conservation and biodiversity maintenance under global change scenarios.